Handling Externalities In Environmental Accounting at XYZ Hospital: A Perspective of Amanah Metaphors - Mauludimah, Listari; Ramadhanikar, Nasiha Sakinah; Baehaqi, Ahmad (Jurnal Akuntansi dan Keuangan Islam, 2023)
This research aims to determine the handling of externalities and their implications for the implementation of environmental accounting at RSUD XYZ (XYZ Hospital) from the perspective of the amanah metaphor. The method used is qualitative research with a case study approach at XYZ Hospital. Data was collected through observation, interviews, and documentation. Data validity was also tested using two types of triangulation. The results show XYZ's Hospital commitment to maintaining environmental balance and reducing the negative impacts of its operations by taking health, safety, and environmental control measures in accordance with Minister of Health Regulation No. 7 of 2019 concerning hospital environmental health. In terms of the application of environmental accounting, XYZ Hospital still does not specifically separate environmental burdens from supply and service burdens. From the perspective of amanah metaphors XYZ Hospital has fulfilled its responsibilities, including those of the trust giver, the trust recipient, and the trust itself. Penelitian ini bertujuan untuk mengetahui penanganan eksternalitas dan implikasinya terhadap penerapan akuntansi lingkungan di RSUD XYZ (RS XYZ) dari sudut pandang metafora Amanah. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan studi kasus di RS XYZ. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Keabsahan data diuji dengan menggunakan dua jenis triangulasi. Hasil penelitian menunjukan bahwa RS XYZ telah menunjukan komitmen dalam menjaga keseimbangan lingkungan dan mengurangi dampak negatif operasionalnya dengan melakukan tindakan kesehatan, keselamatan, dan pengedalian lingkungan sesuai dengan Peraturan Menteri Kesehatan No.7 Tahun 2019 tentang kesehatan lingkungan rumah sakit. Dalam penerapan akuntansi lingkungan, RS XYZ masih belum secara spesifik memisahkan beban lingkungan dari beban persediaan dan jasa. Dari sudut pandang metafora amanah, RS XYZ telah memenuhi tanggung jawabnya, baik kepada pemberi amanah, penerima amanah, dan amanah itu sendiri.